A Systematic Review of Motivational Factors in Developing Speaking Skills Among Indonesian EFL Learners - Larasati, Finza; Saraswaty, Dwi Rara; Eddy Haryanto; Sulistiyo, Urip (PPSDP International Journal of Education, 2024)
This systematic review aims to identify the key motivational factors that influence the development of speaking skills among Indonesian English as a Foreign Language (EFL) learners. Using the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines, five studies were selected for in-depth analysis. The methodology involved the identification, screening, and thematic analysis of research focusing on motivational factors affecting speaking proficiency. The results indicate that both internal factors—such as self-confidence, personal satisfaction, and integrative motivation—and external factors—including teacher support, classroom atmosphere, task structure, and instructional media—play crucial roles in enhancing learners’ motivation to participate in speaking activities. The novelty of this study lies in its focus on the Indonesian EFL context, offering a comprehensive overview of how these motivational factors intersect in this specific educational setting. The study contributes to the field by providing practical recommendations for educators, suggesting that a balanced focus on internal drives and supportive external environments is essential for improving speaking proficiency among Indonesian EFL learners. This review thus highlights the importance of addressing both personal and environmental factors to foster greater participation and confidence in speaking activities.